Children in care: are social workers abusing their authority?. Issue 3 (September 1984) - Foster, J
Abstract : In reply to Dr Benians's article which suggests that social workers at times abuse their authority, three areas can be considered: the broader context of the social work task, the legal process itself, and the contribution made by child psychiatrists.